Perspektif Mahasiswa sebagai Agen Of Change melalui Pendidikan Kewarganegaraan - Faridahtul Jannah; Ani Sulianti (ASANKA: Journal of Social Science And Education, 2021)
This study aims to determine: 1. Student's perspective as an agent of change. 2. The Role of Citizenship Education in forming Students as Agents of Change. The research method used is a qualitative method. Data collection techniques using observation and interviews. The data processing technique uses triangulation. Data analysis used inductive analysis, namely data reduction, unitization and categorization, data display and conclusion drawing. The results showed that: 1. Students as agents of change, namely students have an important role in a change regardless of the level of society or economic status, the intended changes are students who are agents of change, guardians of values, successors of the nation, moral strength and social control. 2. The role of civic education in shaping students as agents of change through several stages, namely: through cognitive, affective, and psychomotor instilled through civic education.